A concise historical atlas of Eastern Europe - Hupchick, Dennis P.; Cox, Harold E. (New York : St. Martin Press, 1996)
Contents: Part I: Early medieval period (to 13th century) -- Part II: Late medieval period (13th-15th centuries) -- Part III: Early modern period (16th-18th centuries) -- Part IV: Period of nationalism (19th century-...)
Keywords: Europe, Eastern -- Historical geography -- Maps; Europe, Eastern -- History